The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1097/tp.0b013e31818aa4b6
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Elimination of Cyclosporine A in Elderly (>65 Years) Kidney Transplant Recipients

Abstract: The clearance of CsA decreased with increasing age. In addition, elderly patients had a significant larger proportion of the whole blood CsA concentration located at the site of action (within T lymphocytes). This indicates that in elderly recipients it might be safe to aim for an even lower whole blood target levels than current guidelines propose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 25 publications
0
34
0
1
Order By: Relevance
“…Agerelated decreased renal clearance of cyclosporine has been demonstrated in elderly kidney transplant recipients. 48 Hypertension, renal dysfunction, and multiple drug interactions are the major concerns when treating a patient with cyclosporine. 49 Although cyclosporine trough level monitoring is generally not used when monitoring patients with psoriasis, it may be indicated when cyclosporine is used long term at doses greater than 3 mg/kg daily 50 and could also be considered for the elderly.…”
Section: Traditional Systemicsmentioning
confidence: 99%
“…Agerelated decreased renal clearance of cyclosporine has been demonstrated in elderly kidney transplant recipients. 48 Hypertension, renal dysfunction, and multiple drug interactions are the major concerns when treating a patient with cyclosporine. 49 Although cyclosporine trough level monitoring is generally not used when monitoring patients with psoriasis, it may be indicated when cyclosporine is used long term at doses greater than 3 mg/kg daily 50 and could also be considered for the elderly.…”
Section: Traditional Systemicsmentioning
confidence: 99%
“…54 A study of cyclosporine in the elderly (>65 years) demonstrated higher cyclosporine concentrations within T-cells. 56 Moreover, CNI elimination was compromised with increasing age.…”
Section: Introductionmentioning
confidence: 99%
“…Most available pharmacokinetic data in the elderly do not reveal any major differences from the drug disposition detected in younger individuals [54]. A more recent pharmacokinetic study in elderly kidney transplant patients has, however, demonstrated that the clearance of cyclosporine decreased with increasing age and that old patients had a significantly larger proportion of the whole blood cyclosporine concentration located in T lymphocytes [55]. Therefore, selection of the cyclosporine dose for an older patient should be made with caution and it should be started at the lowest limit of the therapeutic range.…”
Section: Alternative Treatmentsmentioning
confidence: 95%